2015
DOI: 10.1158/1535-7163.mct-14-0771
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Integrin-Linked Kinase Suppresses Invasion and Metastasis through Downregulation of Epithelial-to-Mesenchymal Transition in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) is the most common malignancy in the kidney. Antiangiogenic targeted therapies inhibit the progression of RCC, but have limited impacts on invasion or metastasis of tumor cells. Integrin-linked kinase (ILK) is a serine/threonine kinase implicated in the regulation of cell growth/survival, cellcycle progression, epithelial-mesenchymal transition (EMT), invasion/migration, and angiogenesis. However, the role of ILK in RCC has not been evaluated. We investigated the role of ILK on cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…MCF-7 and MDA-MB-231 breast cancer cells treated with a combination of suberoylbis-hydroxamic acid (SBHA) and a proteasome inhibitor had significantly higher p53 , Bax, Bcl-xS and Bak protein levels and decreased the Bcl-2 level [91]. A combination of TSA and TRAIL effectively increased caspase-3, -8, and -9 activation and degradation, in human RCC Caki cells [92]. Our results clearly suggested that TSA, PdNPs or the combination of TSA and PdNPs increased the expression of caspase-3 and -9.…”
Section: Resultsmentioning
confidence: 99%
“…MCF-7 and MDA-MB-231 breast cancer cells treated with a combination of suberoylbis-hydroxamic acid (SBHA) and a proteasome inhibitor had significantly higher p53 , Bax, Bcl-xS and Bak protein levels and decreased the Bcl-2 level [91]. A combination of TSA and TRAIL effectively increased caspase-3, -8, and -9 activation and degradation, in human RCC Caki cells [92]. Our results clearly suggested that TSA, PdNPs or the combination of TSA and PdNPs increased the expression of caspase-3 and -9.…”
Section: Resultsmentioning
confidence: 99%
“…19–21 Additionally, ILK has been shown previously to activate MLC through phosphorylation, 13,14 thereby affecting cell adhesion and migration. Studies have demonstrated previously that ROCK kinase also regulates MLC phosphorylation; thus, MLC may serve as an important signaling node in regulating cancer cell motility, potentially being targeted by T315.…”
Section: Discussionmentioning
confidence: 99%
“…EMT-TF such as snail, slug and ZEB1 are the spotlight of EMT investigation [13]. Upregulation of ZEB1 has been observed in various cancers and the expression of ZEB1 is significantly correlated to tumor grade and lymphatic or distant metastasis [22][23][24]. Previous studies showed that ZEB1 induces EMT by binding to the promoter of E-cadherin and depressing the expression level of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%